Comparison of Monte Carlo simulation of gamma ray attenuation coefficients of amino acids with XCOM program and experimental data - Elbashir, B.O.; Dong, M.G.; Sayyed, M.I.; Issa, Shams A.M.; Matori, K.A.; Zaid, M.H.M. (Results in physics, 2018)
•The (μ/ρ), (Zeff) and (Ne) of some amino acids were calculated using MCNP5 simulations in the energy range 0.122–1.330 MeV.•The values of mean free path (MFP), μ/ρ, Zeff, and Ne were calculated using MCNP5 program and compared with the XCOM results.•MCNP5 code provides good photon interaction parameters for amino acids. The mass attenuation coefficients (μ/ρ), effective atomic numbers (Zeff) and electron densities (Ne) of some amino acids obtained experimentally by the other researchers have been calculated using MCNP5 simulations in the energy range 0.122–1.330 MeV. The simulated values of μ/ρ, Zeff, and Ne were compared with the previous experimental work for the amino acids samples and a good agreement was noticed. Moreover, the values of mean free path (MFP) for the samples were calculated using MCNP5 program and compared with the theoretical results obtained by XCOM. The investigation of μ/ρ, Zeff, Ne and MFP values of amino acids using MCNP5 simulations at various photon energies when compared with the XCOM values and previous experimental data for the amino acids samples revealed that MCNP5 code provides accurate photon interaction parameters for amino acids.